Determining environmental predictors of subjective feeling of depressive symptoms among Polish medical students - Paulina Drożak; Łukasz Bryliński; Agata Bura; Piotr Duda; Katarzyna Augustowska; Grzegorz Mizerski (Kazimierz Wielki University, 2020)
Introduction and objective. Depression is a disease that impairs daily functioning. According to research, as much as 27.2% of medical students suffer from depression or show depressive symptoms and 11.1% of them experience suicidal ideation. The aim of the research was to investigate the occurrence of subjective feeling of depressive symptoms among Polish medical students during the course of their medical studies and to determine predictors of this phenomenon that are related to student's environment. Material and method. A total of 1023 medical students from each year of medical education and different Polish universities took part in the study. The research tool was an author's questionnaire. Obtained data was subjected to a statistical analysis. To assess the relationship between two variables, the chi-square test of independence was used. The level of significance was set at p < 0.05. Results. The statistical analysis showed that most respondents (52.79%) had noticed symptoms that might had pointed to depression during their medical studies. A statistically significant link was found between subjective feeling of depressive symptoms during the course of medical studies and: mother's level of education, relationship with parents, relationship with siblings, relationship with friends, knowing a person that one could count on in a difficult situation, knowing a person in which one could trust with all their problems, frequent feelings of loneliness and feeling that one doesn't participate in social gatherings often enough. Conclusions. The prevalence of subjective feeling of depressive symptoms among medical students is high. Results suggest that good relationships with others are important in prevention of depression.